Importance of early and deeper responses to long-term survival in CML patients: Implications of BCR-ABL testing in management of CML in Indian setting - Mohan B. Agarwal (Indian Journal of Medical and Paediatric Oncology)
The prognosis of patients with chronic myeloid leukemia (CML) has changed radically since the advent of imatinib mesylate, a selective inhibitor of BCR-ABL tyrosine kinase. Shortly thereafter, more potent BCR-ABL inhibitors (dasatinib and nilotinib) were introduced for use in patients resistant to or intolerant of imatinib. All three drugs are now approved for initial therapy for chronic phase CML. Response to tyrosine kinase inhibitor (TKI) treatment is assessed with standardized quantitative reverse transcriptase polymerase chain reaction (Q-RTPCR) and/or cytogenetics at 3, 6 and 12 months. Clinical trials have clearly demonstrated that early and deeper cytogenetic and molecular response to TKI therapy is associated with lower rate of disease progression and improved long-term outcomes. In recent times, molecular response as determined by BCR-ABL transcript levels at defined time points is rapidly gaining popularity as a predictive marker for subsequent outcomes in CML. Optimal response is defined as BCR-ABL transcript levels of ≤10% at 3 months, <1% at 6 months, and ≤0.1% from 12 months onward while >10% at 6 months and >1% from 12 months onward define failure. Patients who do not achieve molecular milestones at 3 or 6 months with 3 months being highly predictive are less likely to achieve cytogenetic responses eventually; early identification of such patients who have a low probability of achieving an adequate response are thus candidates for alternative treatment. Review of literature by electronic search of MEDline, Google Scholar was done using keywords and data was identified and systematically evaluated.